EFEKTIVITAS LATIHAN HILL SPRINT DALAM MENINGKATKAN DAYA LEDAK OTOT TUNGKAI DAN KECEPATAN MAKSIMAL PELARI 400 METER PADA MAHASISWA PKO UNIVERSITAS SULAWESI TENGGARA - Muh. Yasa; La Ode Ahmad Yusran; Dila Savira; Agus Kurniadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of hill sprint training in improving leg muscle explosive power and maximum speed of 400-meter runners among students of the Sports Coaching Education (PKO) study program at Universitas Sulawesi Tenggara. Explosive power and maximum speed are two dominant biomotor components that determine 400-meter running performance, yet many student athletes still show suboptimal achievement in both components. This research used a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 30 students selected through total sampling. Leg muscle explosive power was measured using the standing broad jump test and maximum speed was measured using the 30-meter sprint test. Treatment was given in the form of hill sprint training for 16 sessions with a frequency of three times per week. Data were analyzed using the paired sample t-test after fulfilling the normality prerequisite test. The results showed a significant increase in leg muscle explosive power (t = 11.24; p = 0.000 < 0.05) with an average increase of 7.7%, and a significant increase in maximum speed indicated by a decrease in 30-meter sprint time (t = 9.86; p = 0.000 < 0.05) with an average improvement of 4.6%. Thus, hill sprint training is effective in improving leg muscle explosive power and maximum speed of 400-meter runners.